Application of the Comment Poster Method with Media Comics to Increase Student Values of Grade 7 E in Aqidah Akhlak Subjects in Ma'arif 1 Ponorogo Middle School Academic Year 2018-2019. - Noor Syahid; Shofwan Al Muzani (At-Ta'dib, 2019)
Aqidah Akhlak lessons subject includes two things: first educating students to behave in accordance with Islamic values and morals, secondly educating students to study the material of Islamic teachings. Learning about Aqidah akhlah subject matter should have been taught since the child was born into this world to an educational level by applying various learning strategies. The Prophet has exemplified the learning methods that can be applied in educating the morals of the Companions as well as the Bil Hikmah method, Mauidzah hasanah method, Mujadalah method, the method of motivation, asking questions and throwing questions method, demonstrations method, stories method, imagery method, and rewards and punishments method. the inability of educators to choose methods or errors in the use of methods is often the trigger for not maximizing learning outcomes. In this study the researcher used the Poster comment method. This method aims to increase creativity and encourage students to reason with the problems faced. Based on the results of observations at Ma'arif 1 Ponorogo Middle Schoole the researchers found that the methods often used by teachers at the school were lecture and question and answer methods. This method affects the lack of attention of students to the teacher when explaining the lesson because of the monotonous method. It was found that of the 29 students who took the exam only 45% of students reached the KKM 75 standard. It was expected to improve learning values, and the learning activeness of 7th grade students of Ma'arif 1 Ponorogo Middle School so as to accelerate the achievement of learning goals